The Role of Media in Highlighting Violations of the Protection of Journalists During Armed Conflicts from the Perspective of Journalists and Media Professionals: A Field Study (Al-Farooq Journal of Sciences, 2026)
The study aimed to identify the role of media in highlighting violations of journalists’ protection during armed conflicts from the perspective of journalists and media professionals in Tripoli. The study adopted the descriptive analytical approach and used a questionnaire to collect data from a purposive sample of 40 respondents. The data were analyzed using frequencies, percentages, means, standard deviations, Cronbach’s alpha, Pearson correlation, and linear regression. The findings showed that the role of media was high, with an overall mean of 3.79. The level of highlighting violations of journalists’ protection was also high, with a mean of 3.98, while the obstacles were at a moderate level. The results also revealed a statistically significant relationship and effect of media in highlighting these violations. The study recommended strengthening media coverage, documenting violations, and supporting the protection of journalists.
Keywords: Media, Journalists’ Protection, Armed Conflicts, Violations, Journalists and Media Professionals